2023
DOI: 10.1007/s10745-023-00399-9
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Community-based Environmental Peacebuilding in Cesar, Colombia

Abstract: In conflict studies, environmental peacebuilding (EPB) has become an established concept to explain how environmental cooperation among opposing parties provides a platform for peacebuilding. EPB literature has been shaped predominantly by political science perspectives, initially with a focus on interstate conflicts, and ecological dynamics have received little attention to date. Building on the Social-Ecological Systems Framework (SESF), we develop a framework for community-based EPB and test it in post-conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…EP thus stands for a concept that addresses the need to take environmental protection into account in initiatives for conflict resolution at the local level in Colombia. It is well recognized in the literature that the integration of communities is a pre-condition to avoid negative externalities of both natural conservation projects and peacebuilding initiatives (e.g., Hachmann et al, (2023). However, more often than not, political measures and interventions are based only on one-sided data and perspectives, often mirroring academic disciplinary divides and eclipsing local narratives, as Ansari et al (2023) have shown in a meta-analysis on communication with local communities across the globe.…”
Section: Conclusion: Community-based Solutions For Environmental Conf...mentioning
confidence: 99%
“…EP thus stands for a concept that addresses the need to take environmental protection into account in initiatives for conflict resolution at the local level in Colombia. It is well recognized in the literature that the integration of communities is a pre-condition to avoid negative externalities of both natural conservation projects and peacebuilding initiatives (e.g., Hachmann et al, (2023). However, more often than not, political measures and interventions are based only on one-sided data and perspectives, often mirroring academic disciplinary divides and eclipsing local narratives, as Ansari et al (2023) have shown in a meta-analysis on communication with local communities across the globe.…”
Section: Conclusion: Community-based Solutions For Environmental Conf...mentioning
confidence: 99%
“…Chavez-Miguel et al, 2022;Hellin et al, 2018;Lo¨hr et al, 2021) have shown how bottom-up collective action for resource management can contribute to the formation of community capabilities and the strengthening of social cohesion, both crucial to EPB (Johnson et al, 2021). However, EPB theory recognises that a lack of local capacities towards facilitating climate adaptation that targets structural and institutional drivers of conflict is a significant barrier for collective action (Hachmann et al, 2023;Oliver et al, 2023). In this study, participants in settings characterised by low social cohesion recognised an additional challenge in fostering collective action, an observation that has been reported elsewhere (Akter, 2020;Surtiari et al, 2017).…”
Section: Opportunities For Programming Epbmentioning
confidence: 99%
“…EPB interventions hence require the support of formal policy processes and the willingness of government actors to recognise the value of conflict and advocate for reforms. While government actors are commonly reported as required but missing in EPB processes (Hachmann et al, 2023), their presence is also recognised to increase power asymmetries, which hinders environmental cooperation and local ownership (Ide, 2020). Addressing this trade-off requires identifying highly legitimate political actors that can support in navigating institutional networks marked by low legitimacy.…”
Section: Barriers To Programming Epbmentioning
confidence: 99%